Integration Of Islamic Values And Banjar Local Wisdom In Digital Transformation: Evaluating Online Learning At Islamic Higher Education Institutions In South Kalimantan - Assyauqi, Moh. Iqbal; Andini, Yokke; Hamdie, M. Ilham Masykuri (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2022)
In the context of the ongoing digital transformation of education, particularly in Islamic higher education in South Kalimantan, Indonesia, the integration of information and communication technology (ICT) presents both opportunities and challenges. This study aims to evaluate the implementation of online learning in three Islamic universities during the COVID-19 pandemic, focusing on how Islamic values and Banjar local wisdom are integrated into digital education. A qualitative case study approach was used, employing the CIPP (Context, Input, Process, Product) evaluation model. Data were gathered through interviews, observations, and document analysis from lecturers, policymakers, and students at UIN Antasari Banjarmasin, STAI Rasyidiyah Khalidiyah Amuntai, and STAI Al-Falah Banjarbaru. The findings reveal varied levels of preparedness and success in implementing online learning, with UIN Antasari demonstrating a more comprehensive approach, supported by better infrastructure and effective digital platforms. In contrast, private institutions faced challenges related to internet access, limited human resources, and inadequate technological infrastructure. Despite these disparities, all institutions made efforts to incorporate Islamic values such as ta'awun (mutual assistance) and akhlaq (good character), along with Banjar local wisdom, into their pedagogical approaches. The study highlights the importance of continuous evaluation and investment in infrastructure to ensure that digital transformation in Islamic higher education remains inclusive, culturally relevant, and aligned with local values.